Characterization of Blue Compounds Produced from Interaction between Cobalt Oxide and Kaolin Ore in Presence of Sodium Carbonate at Elevated Temperatures - Amin, R.S. (Asian Journal of Chemistry, 2010)
The reactions in ternary mixtures of sodium carbonate, hydrated cobalt chloride and kaolin at 1000º and 1300ºC were examined by X-ray diffraction patterns and diffuse reflectance spectrometry. The effect of addition of different quantities of sodium carbonate to kaolin on the release of silica, alumina and some sodium aluminosilicate compounds such as mullite, nepheline, carneigieite (low form) and natrodavyne (high form) was investigated. The factors which affect the formation of blue compounds such as cobalt aluminate, cobalt silicate and sodium cobaltate are discussed in the light of results obtained from both X-ray and diffuse reflectance spectrometry.